2018
DOI: 10.3389/fmicb.2018.00216
|View full text |Cite
|
Sign up to set email alerts
|

Recent Insights on Biological and Ecological Aspects of Ectomycorrhizal Fungi and Their Interactions

Abstract: The roots of most terrestrial plants are colonized by mycorrhizal fungi. They play a key role in terrestrial environments influencing soil structure and ecosystem functionality. Around them a peculiar region, the mycorrhizosphere, develops. This is a very dynamic environment where plants, soil and microorganisms interact. Interest in this fascinating environment has increased over the years. For a long period the knowledge of the microbial populations in the rhizosphere has been limited, because they have alwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 127 publications
0
13
0
1
Order By: Relevance
“…In the present study, we attempted to mimic the field condition of a relatively long-lasting drought period together with a short period of heat stress (heat shock), which usually takes place at mid-day (combined drought and heat shock), and the combination of a drought period with more prolonged heat stress, which is a regular occurrence in semi-arid and hot growing regions. Arbuscular mycorrhizal fungi establish mutualistic interactions with more than 80% of all plant species, providing a direct physical link between the soil and plant roots [20,40,41]. AMF is one of the most used biological agents in boosting plant growth, helping in photosynthesis, and enhancing tolerance to biotic and abiotic stresses [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we attempted to mimic the field condition of a relatively long-lasting drought period together with a short period of heat stress (heat shock), which usually takes place at mid-day (combined drought and heat shock), and the combination of a drought period with more prolonged heat stress, which is a regular occurrence in semi-arid and hot growing regions. Arbuscular mycorrhizal fungi establish mutualistic interactions with more than 80% of all plant species, providing a direct physical link between the soil and plant roots [20,40,41]. AMF is one of the most used biological agents in boosting plant growth, helping in photosynthesis, and enhancing tolerance to biotic and abiotic stresses [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the plant has an antioxidant defense system to prevent oxidative stress consisting of several antioxidant enzymes such as superoxide dismutase (SOD); ascorbate peroxidase (APX); catalase (CAT) and glutathione reductase (GR); and non-enzymatic antioxidants like ascorbic acid, reduced glutathione (GSH), and tocopherol to scavenge excessive ROS [17,18]. Arbuscular mycorrhizal fungi (AMF) belonging to Phylum Glomeromycota are one of the most important microorganisms that form a symbiotic relationship with more than 80% of land plants [19,20]. Several studies have shown that AMF can enhance the growth of the host plant through improving soil structure, nutrient, and water uptake [7,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of ECM involves complex developmental reprogramming of host tree morphology, including enhanced LR initiation (Rincón, Priha, Sotta, Bonnet, & Le, ; Tranvan, Habricot, Jeannette, Gay, & Sotta, ), root hair decay (Horan et al, ; Béguiristain and Lapeyrie, ), and elongation of epidermal and cortical cells (Horan et al, ; Kottke & Oberwinkler, ). Apoplastic hyphal penetration is accompanied by changes in plant and fungal cell wall composition (Mello & Balestrini, , and references therein). These changes result in the aggregation of fungal hyphae and their adhesion to the plant cell wall (Laurent et al, ; Tagu et al, ; Tagu & Martin, ), hemicellulose and pectin degradation (Sillo et al, ; Veneault‐Fourrey et al, ), and plant cell wall expansion and de novo biogenesis (Luo et al, ; Sebastiana et al, ; Veneault‐Fourrey et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of ECM involves complex developmental reprogramming of host tree morphology, including enhanced LR initiation (Rincón, Priha, Sotta, Bonnet, & Le, 2003;Tranvan, Habricot, Jeannette, Gay, & Sotta, 2000), root hair decay (Horan et al, 1988;Béguiristain and Lapeyrie, 1997), and elongation of epidermal and cortical cells (Horan et al, 1988;Kottke & Oberwinkler, 1987). Apoplastic hyphal penetration is accompanied by changes in plant and fungal cell wall composition (Mello & Balestrini, 2018, and references therein).…”
mentioning
confidence: 99%
“…ECM hosts are mostly woody species belonging to Betulaceae , Fagaceae , Dipterocarpaceae , Myrtaceae , Pinaceae , Salicaceae , Cupressaceae , Rosaceae , Fabaceae , Aceraceae , Euphorbiaceae , and Ulmaceae , whilst there are up to 20,000 basidiomycetous, ascomycetous and Mucoromycotina fungi involved in this symbiosis ( Rinaldi, Comandini & Kuyper, 2008 ; Tedersoo, May & Smith, 2010 ). Climatic factors have been suggested as the main drivers of ECM diversity and distribution globally, and the species richness of ECM fungi peak at mid-latitudes, especially in temperate forests and Mediterranean biomes of the Northern Hemisphere i.e., where pine forests are the dominant vegetation ( Tedersoo et al, 2014 ; Mello & Balestrini, 2018 ). Environmental and host factors have been shown to drive ECM diversity across the European forests ( Van der Linde et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%